FORMATION OF PROFESSIONAL READINESS OF STUDENTS OF PEDAGOGICAL UNIVERSITIES IN TEACHING PRESCHOOL CHILDREN IN PRESCHOOL EDUCATIONAL INSTITUTIONS IN DECORATIVE DRAWING (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The author in his article reveals the step-by-step process of professional readiness of students of pedagogical universities to teach children decorative and applied arts of preschool children in preschool institutions.